Red Sonja [videorecording (Blu-Ray)] - Lutz, Matilda; Sheehan, Robert, 1988-; Day, Wallis, 1994-; Pasqualino, Luke, 1989- (Samuel Goldwyn Films, 2025)
Enslaved by an evil tyrant who wishes to destroy her people, barbarian huntress Red Sonja must unite a group of unlikely warriors to face off against Emperor Draygan and his deadly bride, Dark Annisia.